Levantamento florístico das espécies de trepadeiras na Reserva Biológica das Perobas, região noroeste do Paraná - Crespão, Laianne Mayara Pezenti (2013)
In Parana there are few studies related to vines associated with Semideciduous Forest.. There are only two larger Conservation Units in Semideciduous Forest in this State, and the Reserva Biológica das Perobas (Rebio) is the second largest. This study aimed to survey the flora of species of vines as well as dispersal syndromes and climbing habit recorded in the ReBio das Perobas, in Tuneiras do Oeste and Cianorte, Paraná. The samples in ReBio was conducted in the period of August 2011 to July 2013, taking weekly. The dispersal syndromes, in the same way that the classification of climbing habit, followed those of field observation, consultation records present in the Herbarium HCF, morphological analysis (flower, fruit and seed) and literature review. Were recorded in Reserva Biológica das Perobas, 85 species of vines, distributed on 30 botanical families. The richest families were registered Bignoniaceae (15), Fabaceae e Malpighiaceae (8), Apocynaceae (7) e Sapindaceae (6), and these five families are responsible for 52% of the recorded species. Regarding dispersal syndromes, the most frequent was anemochory with 49 species of vines, representing 58% of all species recorded in this study. The predominant climbing habit was the scandent, with 29 species of vines, where 35% of these species belong to the families Fabaceae and Malpighiacea. There were two unpublished records of vines to Paraná, both Malpighiaceae: Carolus chlorocarpus and Heladena multiflora. Also recorded were three species of rare creepers: Temnadenia violacea (Apocynaceae), Passiflora miersii (Passifloraceae) and Phanera microstachya (Fabaceae).It’s strongly recommended the continuation of studies on vines in this conservation area.